Students' perceptions of the Malaysian nationhood course in strengthening patriotism among younger generation - Ku Samsu, Ku Hasnita; Ismail, Mohd. Mahadee; Adnan, Zatul Himmah; Lee, Yok Fee; Ab Majid, Arfah; Ab Razak, Ratna Roshida (Human Resource Management Academic Research Society, 2022)
Patriotism-based courses at the tertiary level, such as Malaysian Nationhood or similar are very important to strengthen the patriotism among the younger generation. However, the course is not fully offered to local students in all institutions of higher learning, especially in private universities. On the other hand, there are compulsory courses offered in institutions of higher learning, namely Internalization of Ethics and Civilization and Philosophy and Current Issues, which are expected to absorb the content of the Malaysian Nationhood course or similar. However, the course content does not reflect the important aspects of Malaysia. Therefore, the perception of students who have taken the Malaysian Nationhood course or similar on its ability to strengthen patriotism among the younger generation is very important because they have experienced studying the course. Thus, this quantitative study will examine their perceptions in that context. The study sample consisted of 800 respondents who had attended the Malaysian Nationhoon course from Universiti Putra Malaysia and Universiti Pendidikan Sultan Idris. Based on the descriptive analysis, the study found that students' perception is very positive towards the Malaysian Nationhood Course in strengthening the patriotism among the younger generation. In this regard, it is appropriate that such courses be made compulsory in all institutions of higher learning to ensure the integrity of the patriotism of the country's next generation.